Informality in policymaking : weaving the threads of everyday policy work - Garner-Knapp, Lindsey; Mason, Joanna; Mulherin, Tamara; Visser, E. Lianne (Emerald Publishing Limited, 2024)
This book contains an Open Access chapter. Public policy actors spend considerable time writing policy, advising politicians, eliciting stakeholder views on policy concerns, and implementing initiatives. Yet, they also 'hang out' chatting at coffee machines, discuss developments in the hallway walking from one meeting to another, or wander outside to carparks for a quick word and to avoid prying eyes. Rather than interrogating the rules and procedures which govern how policies are made, this volume asks readers to begin with the informal as a concept and extend this to what people do, how they relate to each other, and how this matters. Emerging from a desire to enquire into the lived experience of policy professionals, and to conceptualise afresh the informal in the making of public policy, Informality in Policymaking explores how informality manifests in different contexts, spaces, places, and policy arenas, and the implications of this. Including nine empirical chapters, this volume presents studies from around the world and across policy domains spanning the rural and urban, and the local to the supranational. The chapters employ interdisciplinary approaches and integrate creative elements, such as drawings of hand gestures and fieldwork photographs, in conjunction with ethnographic 'thick descriptions'. In unveiling the realities of how policy is made, this deeply meaningful and thoughtfully constructed collection argues that the formal is only part of the story of policymaking, and thus only part of the solutions it seeks to create. Informality in Policymaking will be of interest to researchers and policymakers alike.
Includes index.
Keywords: Environmental policy.; Political Science -- Public Policy -- Environmental Policy.; Environmental policy and protocols.; elektronické knihy; electronic books